Selected Papers from the 5th International Electronic Conference on Sensors and Applications - Falcone, Francisco; Mariani, Stefano; Ciucci, Francesco; Lehmhus, Dirk; Messervey, Thomas B.; Vallan, Alberto; Bosse, Stefan (MDPI - Multidisciplinary Digital Publishing Institute, 2020)
This Special Issue comprises selected papers from the proceedings of the 5th International Electronic Conference on Sensors and Applications, held on 15-30 November 2018, on sciforum.net, an online platform for hosting scholarly e-conferences and discussion groups. In this 5th edition of the electronic conference, contributors were invited to provide papers and presentations from the field of sensors and applications at large, resulting in a wide variety of excellent submissions and topic areas. Papers which attracted the most interest on the web or that provided a particularly innovative contribution were selected for publication in this collection. These peer-reviewed papers are published with the aim of rapid and wide dissemination of research results, developments, and applications. We hope this conference series will grow rapidly in the future and become recognized as a new way and venue by which to (electronically) present new developments related to the field of sensors and their applications.